1978
DOI: 10.1007/bf02034689
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial injury by nicotine and its prevention

Abstract: Nicotine administered i.v. or p.o. in doses above 0.0125 mg/kg to the rat caused a highly significant increase in circulating anuclear carcasses of endothelial cells estimated by an original method. This effect of nicotine was completely prevented by a prior oral administration of the flavonoids hydroxyethylrutosides (HR) or Mono-7-HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 1 publication
1
25
0
2
Order By: Relevance
“…In addition, no formed elements except anuclear endothelial cells were present, so that no differentiation was involved. The identification of the elements as endothelial was based mainly on earlier studies (2) using the detachment of cells by 1 2 Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no formed elements except anuclear endothelial cells were present, so that no differentiation was involved. The identification of the elements as endothelial was based mainly on earlier studies (2) using the detachment of cells by 1 2 Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…The high desquamating effect of nicotine on the endothelium was demonstrated in our re cent experimental study in rats (1). Nicotine was given at very low doses corresponding to a fraction of the amount absorbed by smoking one cigarette.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in the results of these two studies suggests that nicotine was not the factor in cigarette smoke which caused the metabolic changes in the cigarette smoke exposure experiments. However, it must be taken into account that in the present work nicotine reached the lungs via circulation, thus affecting first the endothelial cells responsible for angiotensin II conversion (59); much lower amounts of IV nicotine caused endothelial injury (60). When cigarette smoke is inhaled, nicotine is partly transferred through the alveolar wall and it could thus have better access to the enzymes metabolizing prostaglandin E2.…”
Section: Effect Of Cigarette Smoke On Angiotension I Conversion In Thmentioning
confidence: 99%
“…Second, the bronchoconstrictor response in the intact dog following the inhalation of tobacco smoke, the bronchial arterial injection of nicotine, or the pleural application of nicotine solution can be simulated by the corresponding administration of histamine, so the release of histamine was proposed as the basic mechanism for the bronchoconstriction induced by tobacco and nicotine. Aviado et al (60) investigated the release of histamine during inhalation of cigarette smoke and anoxemia in the heart-lung and intact dog preparation. They suggested that there was a definite release of histamine during the period of anoxia, and that the initial bronchoconstriction initiated by inhalation of cigarette smoke might induce a localized state of anoxia, and this in turn might cause the release of histamine.…”
Section: Effect Of Cigarette Smoking On Histamine Metabolism In the Lungmentioning
confidence: 99%
“…It has been demonstrated that hyperlipidaemia and smoking (Velican, 1978) cause increased endothelial turnover which is nicely reflected by a rather simple test for circulating endothelial cells (Davis et al, 1987) originally described by Hladovec (1978). Recent studies have proven the endothelial nature of these circulating cells (Davis et al, 1985).…”
mentioning
confidence: 99%